Developments and Changes Adversely Affecting Trade Unions in the Hospitality Industry of Zimbabwe - Farai Ncube; Olabanji Oni (AFRICAJOURNALS, 2023)
This article investigates the changes happening in the tourism and hospitality industry adversely affecting the trade unions and their ability to effectively organise and represent fully their member interest in Zimbabwe. The authors argue that the tourism and hospitality industry remains one of the fastest growing sectors within the global economy that is undeniably extremely labour intensive. While there are two officially registered unions namely the Zimbabwe Catering and Hotel Workers Union (ZCHWU) and the Hospitality and Allied Workers Union of Zimbabwe (HAWUZ), the focus has been on the ZCHWU which has ultimate control, having enjoyed monopoly from the traditional one union one industry approach. Through in-depth interviews and focus group discussions findings reveal legislative and demographics changes, adoption of precarious employment, adoption of new technology and the entry of Chinese accused of being anti-unionism and exploitative in nature as some of the major changes. The study exposes poor working conditions ranging from, long working hours, low salaries, poor safety conditions, intimidation, harassment and massive casualisation of labour calling for trade union intervention. Based on the findings the research maintains that trade union remain relevant in the sector, beneficial to both their members, employers and the clients they serve.